RETRACTED: Unleashing the mechanism among salesforce control system, salesforce ambidexterity, and emotional exhaustion to enhance the competitive advantage of organizations - Ahmad, Bilal; Liu, Da; Irfan, Muhammad; Álvarez-García, José (Frontiers in Psychology, 2022)
The service-sales interaction should be aligned within and outside the organization, but many companies are not harvesting the benefits of this technique. In line with the conservation of resources (COR) theory, the current research investigates the impact of the salesforce control system on salesforce ambidexterity (service and sales interface), which eventually leads to emotional exhaustion service-related performance outcomes. We assess the proposed model using cross-sectional data of 321 Pakistani salespeople from B2B organizations and employ structural equation modeling for data analysis purposes. Firstly, the study results show that behavior-based control (BBC) has an inverse influence on salesforce ambidexterity. On the other hand, outcome-based control (OBC) is positively associated with salesforce ambidexterity. In addition, salesforce ambidexterity is positively linked with emotional exhaustion. However, emotional exhaustion has a negative impact on both service innovation implementation and service recovery performance. Finally, the results demonstrate the significant and positive moderating influence of self-efficacy and customer demandingness between exogenous and endogenous constructs. The study is particularly important to B2B sales organizations struggling with the difficulties of salesforce ambidexterity and how they control their sales representatives.